Generalized Miller formulae for quantum anharmonic oscillators - Meyer, Maximilian Tim; Schindlmayr, Arno (Dynamics)
Miller's rule originated as an empirical relation between the nonlinear and linear optical coefficients of materials. It is now accepted as a useful tool for guiding experiments and computational materials discovery, but its theoretical foundation had long been limited to a derivation for the classical Lorentz model with a weak anharmonic perturbation. Recently, we developed a mathematical framework which enabled us to prove that Miller's rule is equally valid for quantum anharmonic oscillators, despite different dynamics due to zero-point fluctuations and further quantum-mechanical effects. However, our previous derivation applied only to one-dimensional oscillators and to the special case of second- and third-harmonic generation in a monochromatic electric field. Here we extend the proof to three-dimensional quantum anharmonic oscillators and also treat all orders of the nonlinear response to an arbitrary multi-frequency field. This makes the results applicable to a much larger range of physical systems and nonlinear optical processes. The obtained generalized Miller formulae rigorously express all tensor elements of the frequency-dependent nonlinear susceptibilities in terms of the linear susceptibility and thus allow a computationally inexpensive quantitative prediction of arbitrary parametric frequency-mixing processes from a small initial dataset.

FreeBeacon: Efficient Communication and Data Aggregation in Battery-Free IoT - Liu, Gaosheng; Yıldırım, Kasım Sinan; Wang, Lin (IEEE Transactions on Mobile Computing)

WATS up? What About Teacher Shortage? International Perspectives from Denmark, Germany, and Sweden - Boström, Lena; Kreienbaum, Maria Anna; Wüllner, Sabrina; Ørsted Andersen, Frans; Bostedt, Göran; Håkansson Lindqvist, Marcia (Teacher Shortage in International Perspectives: Insights and Responses. Non-Traditional Pathways to the Teacher Profession)

Teacher Shortages in Germany – Causes, Countermeasures, and Assessments by Educational Scientists - Kreienbaum, Maria Anna; Wüllner, Sabrina (Teacher Shortage in International Perspectives: Insights and Responses. Non-Traditional Pathways to the Teacher Profession)

Frauen im Akkord. Marianne Herzog als Protokollantin westdeutscher Zustände - Vukadinovic, Vojin Sasa (Zeitschrift für Geschichtswissenschaft)

Künstliche Intelligenz in der Kriegsführung. Überblick, Hoffnungen und Risiken - Hälterlein, Jens (Marxistische Blätter)

Autonome Waffensysteme und Meaningful Human Control - Hälterlein, Jens (Marxistische Blätter)

KI im Krieg. „Wir brauchen mehr kritische Debatten und zivilgesellschaftliches Engagement“ - Hälterlein, Jens (NETZPOLITIK.ORG)

The Reinvention of the human body: Cyborgs, String Figures and New Boundaries - Grewe, Felix (Women and their Body)

Netzwerkanalysen als Bestandteil von Sportentwicklungsplanungen - Meier, Heiko; Peper, Robert; Kukuk, Marc; Wäsche, Hagen

MSL: Multi-class Scoring Lists for Interpretable Incremental Decision-Making - Heid, Stefan; Kornowicz, Jaroslaw; Hanselle, Jonas; Thommes, Kirsten; Hüllermeier, Eyke (Communications in Computer and Information Science)
Abstract A scoring list is a sequence of simple decision models, where features are incrementally evaluated and scores of satisfied features are summed to be used for threshold-based decisions or for calculating class probabilities. In this paper, we introduce a new multi-class variant and compare it against previously introduced binary classification variants for incremental decisions, as well as multi-class variants for classical decision-making using all features. Furthermore, we introduce a new multi-class dataset to assess collaborative human-machine decision-making, which is suitable for user studies with non-expert participants. We demonstrate the usefulness of our approach by evaluating predictive performance and compared to the performance of participants without AI help.

Breaking of the Up‐Down Symmetry of DNA Origami on a Solid Substrate - Velpula, Gangamallaiah; Tomm, Emilia; Shen, Boxuan; Mali, Kunal S.; Keller, Adrian Clemens; De Feyter, Steven (Angewandte Chemie International Edition)
Abstract Controlling the surface orientation of DNA origami nanostructures (DON) is crucial for applications in nanotechnology and materials science. While previous work utilized various DON modifications, simple methods for controlling their landing orientation remain scarce. Here, we demonstrate a straightforward approach to control the adsorption orientation of chiral double‐L (CDL) DON on mica by tuning magnesium ion (Mg 2 ⁺) concentration and exploiting global shape distortions. Using atomic force microscopy (AFM), we analyzed the resulting distribution of the mirror‐image orientations, referred to as S and Z orientations, at both buffer/mica and air/mica interfaces and identified conditions resulting in homogenous CDL orientation of 100% S. These results demonstrate how DON conformation and ionic environments influence DON orientation, offering insights for precise nanostructure deposition.

From Temporary Fixes to Informed Decisions—Design Echelons for Evaluating Workarounds - Reineke, Malte Fabian; Löhr, Bernd; Aßbrock, Agnes; Bartelheimer, Christian; Beverungen, Daniel (International Conference on Business Process Management 2025)

Are numerical or verbal explanations of AI the key to appropriate user reliance and error detection? - Papenkordt, Jörg; Ngonga Ngomo, Axel-Cyrille; Thommes, Kirsten (Behaviour & Information Technology)

Shifting Dynamics: How Generative AI as a Boundary Resource Reshapes Digital Platform Governance - Mayer, Anne-Sophie; Kostis, Angelos; Strich, Franz; Holmström, Jonny (Journal of Management Information Systems)

Distributed and Parallel Low-Diameter Decompositions for Arbitrary and Restricted Graphs - Dou, Jinfeng; Götte, Thorsten; Hillebrandt, Henning; Scheideler, Christian; Werthmann, Julian (16th Innovations in Theoretical Computer Science Conference (ITCS 2025))

Inertial dynamics with vanishing Tikhonov regularization for multobjective optimization - Bot, Radu Ioan; Sonntag, Konstantin (Journal of Mathematical Analysis and Applications)
In this paper we introduce, in a Hilbert space setting, a second order dynamical system with asymptotically vanishing damping and vanishing Tikhonov regularization that approaches a multiobjective optimization problem with convex and differentiable components of the objective function. Trajectory solutions are shown to exist in finite dimensions. We prove fast convergence of the function values, quantified in terms of a merit function. Based on the regime considered, we establish both weak and, in some cases, strong convergence of trajectory solutions toward a weak Pareto optimal solution. To achieve this, we apply Tikhonov regularization individually to each component of the objective function. This work extends results from single objective convex optimization into the multiobjective setting.
Keywords: Pareto optimization; Lyapunov analysis; gradient-like dynamical systems; inertial dynamics; asymptotic vanishing damping; Tikhonov regularization; strong convergence

Promote technology learning using a spiral curriculum – Developing evidence-based concepts for technology education focusing on problem-solving - Schemel, Nele; Tenberge, Claudia (The 42nd Pupils' Attitudes Towards Technology Conference Proceedings 2025)

‚Novellierungen‘ der Novellistik. Der ‚Fall‘ der Novelas ejemplares - Schlieper, Hendrik (Artes)

Auffächerung im Spiegel der Übersetzung und darüber hinaus: La Grande Peur dans la montagne von Charles Ferdinand Ramuz und die beiden deutschen Übersetzungen dieses Romans - Kunert, Irene Dorothea (PhiN Beiheft 40: Verdichtung und Auffächerung. (Übersetzte) Literatur zwischen Präsenz und Virtualität)